GAMBARAN KUALITAS UDARA DI KOTA YOGYAKARTA BERDASARKAN PEMANTAUAN AIR QUALITY MONITORING SYSTEM TAHUN 2019-2020 - Hemida Wahyu Isramadhanti Isramadhanti (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
According to the 2019 Environmental Quality Index report, air quality in the city of Yogyakarta has decreased in the past five years. In connection with concerns about the decline in air quality in the city of Yogyakarta and its negative impact on living things, it is necessary to take steps to monitor air quality. So to find out the description of air quality in Yogyakarta City in 2019 - 2020, it can be reviewed through the Air Quality Monitoring System in the form of the Air Pollutant Standard Index. The results of monitoring air quality parameters have decreased and increased levels. However, based on the monitoring of the Air Quality Monitoring System in 2019-2020, the chemical parameters of air quality (PM10, SO2, CO, O3, NO2) in Yogyakarta City are still classified as